2009
DOI: 10.1371/journal.pone.0004379
|View full text |Cite
|
Sign up to set email alerts
|

Probing Evolutionary Patterns in Neotropical Birds through DNA Barcodes

Abstract: BackgroundThe Neotropical avifauna is more diverse than that of any other biogeographic region, but our understanding of patterns of regional divergence is limited. Critical examination of this issue is currently constrained by the limited genetic information available. This study begins to address this gap by assembling a library of mitochondrial COI sequences, or DNA barcodes, for Argentinian birds and comparing their patterns of genetic diversity to those of North American birds.Methodology and Principal Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
188
5
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(217 citation statements)
references
References 43 publications
23
188
5
1
Order By: Relevance
“…2004; Kerr et al. 2009). Additionally, comparisons of genetic diversity with the two comparison populations – short‐tailed babbler population in Singapore and the Philippine bulbul population in Mount Apo, an area of similar size to Singapore – revealed that the Singaporean olive‐winged bulbul population has the highest genetic diversity of the three.…”
Section: Discussionmentioning
confidence: 99%
“…2004; Kerr et al. 2009). Additionally, comparisons of genetic diversity with the two comparison populations – short‐tailed babbler population in Singapore and the Philippine bulbul population in Mount Apo, an area of similar size to Singapore – revealed that the Singaporean olive‐winged bulbul population has the highest genetic diversity of the three.…”
Section: Discussionmentioning
confidence: 99%
“…2009; Kerr et al. 2009b), divergences in the COX1 gene in birds are congruent with taxonomist‐determined species boundaries.…”
Section: Introductionmentioning
confidence: 86%
“…Recently, DNA barcoding has become an increasingly popular approach to the delimitation of species (Hebert et al, 2003;Blaxter, 2004;Ward et al, 2005Ward et al, , 2009Kerr et al, 2007Kerr et al, , 2009Steinke et al, 2009;Casiraghi et al, 2010). In this approach, a partial sequence of the cytochrome c oxidase subunit I gene (COI) has been standardized as a DNA barcode for the analysis of animal groups, including cryptic species complexes (Hebert et al, 2004a(Hebert et al, , 2004bHubert et al, 2008;Lara et al, 2010;Allcock et al, 2011).…”
Section: Introductionmentioning
confidence: 99%